2002
DOI: 10.1038/417182a
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a factor that links apoptotic cells to phagocytes

Abstract: Apoptotic cells are rapidly engulfed by phagocytes to prevent the release of potentially noxious or immunogenic intracellular materials from the dying cells, thereby preserving the integrity and function of the surrounding tissue. Phagocytes engulf apoptotic but not healthy cells, indicating that the apoptotic cells present a signal to the phagocytes, and the phagocytes recognize the signal using a specific receptor. Here, we report a factor that links apoptotic cells to phagocytes. We found that milk fat glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
1,354
3
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,229 publications
(1,379 citation statements)
references
References 30 publications
17
1,354
3
5
Order By: Relevance
“…For example, PS can be recognized by cell surface receptors including TIM-4 (Kobayashi et al 13 and Miyanishi et al 14 ) and BAI-1. 15 PS can also be recognized by soluble opsonins such as MFG-E8 and Gas6, that are in turn detected by cell surface molecules α V β 3 and TAM receptors, respectively [16][17][18] (Figure 2a). The recognition of PS by phagocytes through various phospholipid detectors is an important molecular step to trigger the engulfment of apoptotic cells, 3 and exemplifies how modification of the phospholipid code on the surface of apoptotic cells can promote their clearance.…”
Section: Box 1 Phospholipids As Key Regulators Of Intracellular Procementioning
confidence: 99%
“…For example, PS can be recognized by cell surface receptors including TIM-4 (Kobayashi et al 13 and Miyanishi et al 14 ) and BAI-1. 15 PS can also be recognized by soluble opsonins such as MFG-E8 and Gas6, that are in turn detected by cell surface molecules α V β 3 and TAM receptors, respectively [16][17][18] (Figure 2a). The recognition of PS by phagocytes through various phospholipid detectors is an important molecular step to trigger the engulfment of apoptotic cells, 3 and exemplifies how modification of the phospholipid code on the surface of apoptotic cells can promote their clearance.…”
Section: Box 1 Phospholipids As Key Regulators Of Intracellular Procementioning
confidence: 99%
“…In contrast, this study dealt with the functional p63 proteins localized to undifferentiated keratinocytes in the basal layer of stratified epithelia and in carcinomas derived from the stage. MFG-E8-L, the mouse-specific long isoform, having a Pro/Thr-enriched domain, facilitates phagocytosis of apoptotic cells by macrophages as demonstrated by recent studies with MFGE8-deficient mice (Hanayama et al, 2002;Hanayama and Nagata, 2005). However, the other isoform, MFG-E8-S, lacking the phagocytosisfacilitating activity is more ubiquitously, abundantly expressed (Watanabe et al, 2005) and expected to facilitate various types of cell-cell interactions.…”
Section: Mfge8mentioning
confidence: 99%
“…Mouse Mfge8 produces MFG-E8-L and MFG-E8-S, in which the former is mousespecific, and the latter conserved among humans and animals (Watanabe et al, 2005). While the L form containing a Pro/Thr-enriched domain facilitates phagocytosis of apoptotic cells by macrophages (Hanayama et al, 2002(Hanayama et al, , 2004, the S form was reported to support the gamete interaction upon fertilization (Ensslin and Shur, 2003). Very importantly, recent studies determined peptide sequences derived from human MFG-E8 as the potential targets for tumor immunotherapy (Carmon et al, 2002;Liu et al, 2005).…”
mentioning
confidence: 99%
“…Many molecules on the phagocyte have been implicated; 24 the recognition of PS on apoptotic cells, with or without the conjunction of intermediary molecules, appears to be important. 20,25,26 The notion that defects in the clearance of apoptotic debris can give rise to a lupus-like pathology has been supported by a number of knockout mouse models; C1q À/À , 27 c-mer À/À9 and most recently MFG-E8 À/À 28 mice. Injection of mutant MFG-E8 (engineered to mask PS and reduce apoptotic cell uptake) also elicits autoimmune responses, particularly when administered along with apoptotic cells.…”
Section: Reactivity Of the Immunizing Antibody (Rn86) Is Shown For Rementioning
confidence: 99%